América llatina '76. - Fundacio Joan Miro, Barcelona; Centro de Arte y Comunicación, Buenos Aires (Barcelona : Fundació Joan Miró, 1977)
Alvaro, Jorge ; de Aquino, Angelo ; Barrios, Alvaro ; Bedel, Jacques ; Benedit, Luis ; Bercetche, Juan ; Bianchedi, Remo ; Caro, Antonio ; Camporeale, Sergio ; Compaired, Héctor ; Cugat, Delia ; D'Alessandro, Horacio ; Davidovich, Jaime ; Dermijian, Jorge ; Dermisache, Mirtha ; Diaz, Luis ; Dujony, Gregorio ; Durante, Armando ; Ehrenberg, Felipe ; Esteves, Mercedes ; Garcia Uriburu, Nicolás ; Glusberg, Jorge ; Gozález, Haroldo ; Gozález Mir, Jorge ; Grippo, Victor ; etc.
América llatina '76 : 59 Artistas Latinoamericanos, Fundació Joan Miró, Barcelona / Centro de Arte y Comunicación de Buenos Aires, Enero 1977
boek